A 400‐Year Ice Core Melt Layer Record of Summertime Warming in the Alaska Range. Issue 7 (13th April 2018) - Winski, Dominic; Osterberg, Erich; Kreutz, Karl; Wake, Cameron; Ferris, David; Campbell, Seth; Baum, Mark; Bailey, Adriana; Birkel, Sean; Introne, Douglas; Handley, Mike
Abstract: Warming in high‐elevation regions has societally important impacts on glacier mass balance, water resources, and sensitive alpine ecosystems, yet very few high‐elevation temperature records exist from the middle or high latitudes. While a variety of paleoproxy records provide critical temperature records from low elevations over recent centuries, melt layers preserved in alpine glaciers present an opportunity to develop calibrated, annually resolved temperature records from high elevations. Here we present a 400‐year temperature proxy record based on the melt layer stratigraphy of two ice cores collected from Mt. Hunter in Denali National Park in the central Alaska Range. The ice core record shows a sixtyfold increase in water equivalent total annual melt between the preindustrial period (before 1850 Common Era) and present day. We calibrate the melt record to summer temperatures based on weather station data from the ice core drill site and find that the increase in melt production represents a summer warming rate of at least 1.92 ± 0.31°C per century during the last 100 years, exceeding rates of temperature increase at most low‐elevation sites in Alaska. The Mt. Hunter melt layer record is significantly ( p  < 0.05) correlated with surface temperatures in the central tropical Pacific through a Rossby wave‐like pattern that enhances high temperatures over Alaska. Our results show that rapid alpine warming has taken place in the Alaska Range for at least a century and that conditions in the tropical oceans contribute to this warming. Plain Language Summary: Warming in mountainous areas affects glacier melt, water resources, and fragile ecosystems, yet we know relatively little about climate change in alpine areas, especially at high latitudes. We use ice cores drilled on Mt. Hunter, in Denali National Park, to develop a record of summer temperatures in Alaska that extends 400 years into the past, farther than any other mountain record in the North Pacific region. The ice core record shows that 60 times more snowmelt occurs today than 150 years ago. This corresponds to roughly a 2°C increase in summer temperature, which is faster than summertime warming in Alaska near sea level. We suggest that warming of the tropical Pacific Ocean has contributed to the rapid warming on Mt. Hunter by enhancing high‐pressure systems over Alaska. Our ice core record indicates that alpine regions surrounding the North Pacific may continue to experience accelerated warming with climate change, threatening the already imperiled glaciers in this area. Key Points: The Alaska Range currently experiences more summertime snowmelt than at any time in the last 400 years Mt. Hunter is warming faster than most lowland sites in south central Alaska Warm conditions in the tropical Pacific Ocean are likely responsible for part of the amplified warming signal observed on Mt. Hunter